The bridges of New Jersey : portraits of Garden State crossings - Richman, Steven M., 1955- (Rutgers University Press, 2005)
New Jersey is sandwiched between the Hudson and Delaware Rivers, with the Raritan, Passaic, and Navesink cutting swaths across it. In spite of the state's relatively small size, over six thousand bridges span its varied landscape. They traverse rivers, streams, railroads, and roadways. Several dozen bridges cut across the Delaware River alone, carrying pedestrian, vehicular, and railroad traffic. Three connect the state to Staten Island. Some are steeped in history, dating back to the colonial era and the Revolutionary war. Others are recognized worldwide for their size or significance.